Study on Freezing-Thawing Failure Process of Natural Damage Sandstone Based on Cellular Automata. (20th June 2022) - Liu, Hui; Xu, Yali; Huang, Huiqi; Han, Senlei; Xu, Hainan
Abstract : Natural damage such as internal cracks, pores, and discontinuous surfaces of rocks induces the formation, expansion, and interaction of mesofractures until macroscopic failure under the action of freeze-thaw and load. The failure process is the evolution of self-organization and has localization characteristics. The CT scanning test of sandstone with different freezing and thawing cycles was carried out. According to the theory of cellular automata analysis, combined with CT image processing technology, the numerical model of the mesostructure of the sandstone constructed with natural damage, and the numerical simulation test of the Brazilian splitting failure of natural damage sandstone was completed under freezing and thawing. The results show that the combination of CT image processing technology and CASRock numerical simulation software can dynamically describe the whole process of initial damage propagation, new crack generation, and penetration of rock containing natural damage under tension in a freeze-thaw environment. Due to random and disordered natural damage inside the rock, gradually changing to an orderly state under freezing and load, the rock shows discontinuous deformation after the plastic deformation reaches a certain degree and gathers at the initial damage expansion. The fracture process of natural damaged rock under freezing and load has continuous-discontinuous deformation characteristics. The existence of initial rock damage causes the rock's localized deformation and failure characteristics. The form and size of the initial damage determine the direction of development of the surface of the sandstone fracture and the coalescence of the crack. The initial damage area of sandstone is expanded due to the freeze-thaw cycle. After loading, the local deformation and failure characteristics caused by initial damage have delay characteristics for penetration of the main cracks in the sandstone, which determines the formation and development direction of secondary cracks in the rock failure process.